The Innovation Originated with Material Procurement: The Introductory Study for Elucidating the Process - Yoshinobu NEMOTO; Taichi KISHIMOTO (AAOS Transactions)
Material procurement could have a key role in originating and leading innovations. Firstly, new materials and suppliers can be searched and sourced by material procurement to reduce their own product price. Then, the consideration and coordination to introduce those new materials generate pressures to bring innovation for other parts of the product and manufacturing technologies as chain reactions. Responding to these pressures, finally, innovative products can be created. These phenomena are highly possible to occur logically. However, to our knowledge, the study attempting to elucidate the theme of this study has hardly ever been seen. In previous studies, though “technology push” and “demand pull” have mainly been focused as origins and causes of innovation processes, material procurement has hardly been focused. In the 21st century, modularizations and globalization of supply chain have been progressing in various industries. Under the circumstances, activities in material procurement for originating innovation are being intensified especially in practitioners such as in electronics industry. Accordingly, in this study, an abstracted hypothesis of innovation process originated with material procurement is proposed as the result of the introductory study.